Empowerment of Remaja Mesjid Raya Limo Kaum in Preserving Culture and Historical Values in Tanah Datar Regency - Beni Putra Hanafi; Muhammad Irsyad; Iswadi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2026)
This study aims to analyze the role of the youth of Masjid Raya Limo Kaum in preserving the cultural and historical values of Nagari Limo Kaum, Tanah Datar Regency. Employing a descriptive qualitative approach, this field research utilized observation, interviews, and documentation as data collection techniques. The findings reveal that the mosque youth are actively involved in various preservation activities, including traditional schools, martial arts training, cultural seminars, and the upkeep of the tomb of the mosque's founding figure. Nevertheless, several challenges persist, such as waning interest among young people in mosque-related activities, low appreciation for elders, and the pervasive influence of technological advancements. This study recommends a synergistic integration of tradition and innovation, particularly through the use of social media to introduce historical values to the younger generation. In doing so, it is hoped that local culture can be preserved and made relevant to the present generation.